First evidence of cynipids from the Oceanian Region: the description of Lithonecrus papuanus a new genus and species of cynipid inquiline from Papua New Guinea (Hymenoptera: Cynipidae, Synergini) - Nieves-Aldrey, J. L.; Butterill, P. T. (Zootaxa, 2014)
Lithonecrus papuanus Nieves-Aldrey & Butterill, a new genus and species of inquiline oak gall wasps (Hymenoptera: Cynipidae: Synergini), is described from material reared from galls on Lithocarpus celebicus (Miq.) Rehd., collected in Papua New Guinea. The new genus and species is the first record of a cynipid from Papua New Guinea and the whole  Oceanian biogeographic region,  and represents the easternmost oriental record of a cynipid wasp (Hymenoptera: Cynipidae). The new genus is similar to Saphonecrus Dalla Torre & Kieffer, and to the recently described Lithosaphonecrus Tang, Melika & Bozsó, but differs from these genera in several important diagnostic characters. Taxonomic affinities and differences with related genera and species and biogeographical implications are discussed.